Konsep Penawaran dalam Studi Ekonomi Syari’ah - Trigatiningtyas, Erike Oktaviani (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2022)
This study aimed to explain how the process of the Islamic economic supply concept and explained how the bidding case was. This study was a quantitative research assisted by literature study techniques. The study results revealed that there were examples of good supply analysis in Islam. The production process that occured efficiently if there was an Islamic economic concept with instruments that were more divided in results than using the practice of interest in conventional economics. So that the findings from this study were expected to be much more in the future. Not only that, it would also be better proven that Islamic economics was a